Pengaruh Pola Asuh Dan Interaksi Teman Sebaya Terhadap Kecerdasan Emosional Anak Di Ra Arif Rahman Hakim Yogyakarta - Putro, Khamim Zarkasih (Al-Athfal: Jurnal Pendidikan Anak, 2015)
This study aims to determine the effect of parenting and interaction among peers on the child's emotional intelligence in RA Arif Rahman Hakim Maguwoharjo, Depok, Sleman, Yogyakarta. This research was conducted in RA Arif Rahman Hakim in September 2015. The population in this study are all parents and students in RA Arif Rahman Hakim amount to 74 students, divided into five classes. Samples were taken randomly, obtained one class, it’s B2 class consisting of 15 students. Data collection techniques used were observation, interviews, and questionnaires. Data analysis techniques in the study using multiple regression analysis with two independent variables.The result showed that: (1) there is a positive influence on parenting for the child's emotional intelligence, (2) there is a positive effect of interaction among peers for the child's emotional intelligence, and (3) there is a positive influence on parenting and interaction among peers together (simultaneously) to the child's emotional intelligence, the real effect of the rate is 47.8%.